How Long Should Grasses of South American Campos Grasslands Rest for Stockpiling Forage? - Risso Barbosa, Marlon; Durante, Martin; Marin, Luciana; Cazzuli, Fiorella; Quadros, Fernando Luiz Ferreira de; Dixon, Rob M.; Correa, Franklin Riet; Jaurena, Martín (MDPI, 2024)
Stockpiling forage (i.e., deferring grazing) is one way to provide forage for livestock during intervals of low pasture growth, but there are trade-offs as nutrient content declines with increasing forage maturity. Phosphorous (P) concentration, crude protein (CP) content and organic matter digestibility (OMD) were evaluated in two C3 and four C4 grasses native to the South American Campos grasslands. These were: Bromus auleticus (BROAUL) and Nasella neessiana (NASNEE) as C3 grasses and Andropogon lateralis (ANDLAT), Mnesithea selloana (MNESEL), Paspalum dilatatum (PASDIL), and Paspalum notatum (PASNOT) as C4 grasses. The grasses were grown in pots during five stockpiling periods (450, 900, 1350, 1800 and 2250 degree days, approximately 20, 40, 60, 80 and 100 days). As the forage deferment increased, the nutritional value decreased more in C4 than in C3 grasses. Short rest periods (approximately 40 days) are recommended for PASDIL and MNESEL, and medium rest periods (approximately 80 days) for ANDLAT and PASNOT. However, the C3 grasses BROAU and NASNEE maintained high P and CP concentrations and may be the most appropriate option for long rest periods (≥100 days). This information is important to manage different Campos grassland communities for the optimal rest period according to the dominant species.